Service charge issue in Malaysian high-rise residential management : An analysis using a fuzzy conjoint model - Nurakmal, Abdullah@ Goh Tuo Ho; Norngainy, Mohd Tawil; Che-Ani, A. I.; Ramly, A.; Daud, M. N. (Academic Journals Inc., USA, 2011)
This paper discusses the results of a study on high-rise residential complexes, with particular attention reference to their financial management. The research focuses on service charges, looking at both sides of the management issue, the amount owners pay and the level of service the management provides. Literature and field surveys indicate that this issue follows a circular argument in which both the property owners and the management corporations are contributory. The root cause seems to be financial. Owners’ failure to keep up payment leads to a shortage of funds and thus the corporation’s capacity to provide quality services, this situation in turn causes dissatisfaction among residents who, consequently, are reluctant to pay the prescribed charges. As a result, management corporations report having difficulty with service charge collection, only 50% of the residential complexes collect half of their fees on time. In addition to the analysis of the difficulties faced in collecting funds, this research also analyses owner satisfaction with service charge collection and complex management systems. The analysis used to analyse the survey is a fuzzy conjoint model, where the results were presented in terms of the linguistic value of ‘agree’. The analysis shows that residents were not satisfied with service charge fees and would like to know how their service charges are disbursed. They also admit to a delay in the payment of their fees. The residents admit to making many complaints about service and that they believe that their service charges are disproportionally high relative to the quality of services provided by their property management company. The findings also showed that no standard method exists for determining the rate for service charges in any high-rise housing complex.